АДАПТАЦИЯ РИСК-МЕНЕДЖМЕНТА К КЛИНИЧЕСКОЙ ПРАКТИКЕ ИНФАРКТА МИОКАРДА - А. М. Назаров; Р. И. Сайфутдинов (SINAPS LLC, 2014)
The review contains an analysis of the literature on the problems of optimization approaches in the treatment of myocardial infarction, as well as methods of risk management. The necessity of the development and implementation of the strategy of risk management in clinical practice of myocardial infarction, as well as tasks that should be solved, managing risk of myocardial infarction. Identified risks and incidents of occupational risks of myocardial infarction.